Europäische Versorgungsstandards für Menschen mit rheumatoider Arthritis: Übersetzung und Kommentierung der von der EULAR unterstützten Vorschläge des eumusc.net durch eine Task Force von DGRh und VRA mit Unterstützung der Deutschen Rheuma-Liga = Standards of care for people with rheumatoid arthritis in Europe : Translation and comments of the eumusc.net recommendations supported by EULAR performed by a national task force of the professional organisations DGRh and VRA supported by „Deutsche Rheumaliga“ - Braun, Jürgen; Lorenz, Hanns-Martin (Zeitschrift für Rheumatologie, 2016)
In a joint initiative by the boards of the German Society for Rheumatology (DGRh) and the Association of Rheumatology Clinics (VRA) the European „standards of care“ for rheumatoid arthritis, recently suggested by the European Musculoskeletal Conditions Surveillance and Information Network (eumusc.net) and supported by the European League Against Rheumatism (EULAR), were translated and annotated. The recommendations include aspects of the management of the disease, actual medical care, and access to information - this includes all types of support people with RA need, and, last but not least communication of the necessary knowledge. Furthermore, health care structures such as the availability of medical staff with relevant expertise are also important.
Gesehen am 19.09.2019